2021
DOI: 10.3389/fphar.2021.721216
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract Is Comparable With Donepezil in Improving Functional Recovery in Alzheimer’s Disease: Results From a Multilevel Characterized Study Based on Clinical Features and Resting-State Functional Magnetic Resonance Imaging

Abstract: Background: Ginkgo biloba extract (GBE) and donepezil have been reported to be effective in patients with Alzheimer’s disease (AD). Nonetheless, how these drugs impact spontaneous brain activities and how they consequently improve functional recovery are currently unclear.Objectives: This study was to explore the efficacy of GBE vs. donepezil and their add-on efficacy on functional recovery and the adaption of spontaneous brain activities following pharmacologic treatment in patients with AD.Methods: Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…The brain regions with significantly increased ReHo values involved widespread frontal lobe regions. Another study ( Zheng et al, 2021 ) has found that patients with Ginkgo biloba extract showed significantly decreased ALFF in the left parahippocampal gyrus, FFG.l, right gyrus rectus, and right superior frontal gyrus, while an increase in ALFF in the right middle temporal gyrus. Such brain activity change patterns are not consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The brain regions with significantly increased ReHo values involved widespread frontal lobe regions. Another study ( Zheng et al, 2021 ) has found that patients with Ginkgo biloba extract showed significantly decreased ALFF in the left parahippocampal gyrus, FFG.l, right gyrus rectus, and right superior frontal gyrus, while an increase in ALFF in the right middle temporal gyrus. Such brain activity change patterns are not consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on nootropics revealed nootropics to have minimal, if any, effects on the prevention of cognitive decline. Most studies were either examined over a relatively short follow-up time or conducted with a limited number of subjects, and many of them focused on nootropic monotherapy rather than concomitant use with ChEI [ 6 , 9 , 10 , 17 , 23 , 24 , 25 ]. This study aimed to compare the nootropics and ChEI combination with ChEI monotherapy in an attempt to validate the effectiveness of nootropics in association with ChEI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PerAF approach indicates the ratio of frequency-domain in blood oxygen level-dependent signal in the resting-state to average signal strength for a specific period. Following the pre-processing, the PerAF method was computed ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some covariates, such as age, gender, and education level, were regressed. For the preliminary comparison results of the average PerAF values between the two groups, the multiple-comparison correction based on the Gaussian random field theory (GRF, two-tailed, cluster-wise p < 0.05, voxel-wise p < 0.001) was further conducted ( 30 ). Previous studies reported that, compared with the Bonferroni correction and false discovery rate (FDR), GRF could reduce the false-positive rate and improve statistical power by utilizing the spatial information of fMRI data ( 31 ).…”
Section: Methodsmentioning
confidence: 99%